HUMAN RESOURCE DEVELOPMENT STRATEGY IN NORTH PADANG LAWAS REGENCY TO SUPPORT REGIONAL DEVELOPMENT - Nursaimatussaddiya; Christin Natalia Sianipar; Pretty Naomi Sitompul (CV. Radja Publika, 2026)
Human resource development is an important factor in supporting regional development because the quality of people determines the success of development programs, public services, and local economic growth. This study discusses the strategy of human resource development in North Padang Lawas Regency in supporting regional development. The main focus of this study includes education, health, skills training, employment opportunities, community empowerment, digital literacy, and local government capacity. This study uses a qualitative descriptive method with secondary data obtained from official publications, statistical reports, books, journals, and relevant institutional sources. The results show that human resource development in North Padang Lawas Regency has shown positive progress, as reflected in the increase of the Human Development Index from 71.69 in 2020 to 74.16 in 2024. However, continuous efforts are still needed to improve the quality of education, strengthen health services, expand vocational training, create employment opportunities, and increase community participation. Human resource development strategies must be implemented in an integrated and sustainable manner by involving the local government, educational institutions, training centers, health institutions, private sectors, and community organizations. By improving the quality of human resources, North Padang Lawas Regency is expected to increase regional competitiveness, improve public welfare, and achieve sustainable regional development.